Performance of Some Thai Weed Extracts on Antioxidants and Atherosclerosis- Related Enzymes - U-Yatung, Sunisa; Suebsaiprom, Wanida; Pornprom, Tosapon; Chompoo, Jamnian (AGRIVITA, Journal of Agricultural Science, 2020)
This study used several methods to investigate the performance of aqueous extracts from some Thai weeds on antioxidants and atherosclerosis-related enzyme inhibitors. The inhibitory effect of aqueous extracts was expressed as the percentage of inhibition at a concentration of 500 μg/ml. GS-MS analysis was used to identify isolated compounds in sample extracts. The antioxidant activities were investigated using DPPH, ABTS, nitric oxide radical scavenging and oxidation of LDL. The results showed that the aqueous extract from the leaves of Bidens pilosa had greater inhibitory effects than others (71.23, 57.89 and 50.09%, respectively, except ABTS); however, B. pilosa had weaker inhibition than the positive controls. Pancreatic lipase and 15-lipoxygenase (15-LO) had inhibitory effects regarding atherosclerosis-related enzyme activities. The research found that Euphorbia hirta had stronger inhibitory activity against PL and 15-LO than other extracts (30.47 and 84.66%, respectively). Moreover, E. hirta had similar activity to quercetin against 15-LO (89.25%). Finally, isolated compounds were referred by GC-MC, the result presented more than 30 phenolic compounds and quite different characters, which might widely encouraged in antioxidants and inhibition of enzymatic activities. The results indicated that B. pilosa and E. hirta were the sources of bioactive compounds as antioxidants and anti-atherosclerosis, respectively.